2019
DOI: 10.1037/dev0000620
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in the development of a preference for scarce objects.

Abstract: Adults value scarce objects, such as rare precious stones and limited edition items. This valuation may derive from an understanding of market forces and sociological considerations, but it may also be related to more basic cognitive and motivational processes. The present studies addressed these possibilities by investigating the development and cross-cultural prevalence of a preference for scarce objects. Children (N = 366) from Israel and Taiwan, ranging from 4 to 11 years of age, were given a choice betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…This difference could potentially explain the change in infants’ responding from Study 1 to Study 2. In fact, a similar change is seen when comparing 4‐year‐olds’ responses in Study 3 here—wherein all stickers were presented as coming from a single set—to the responses of 4‐year‐olds in Diesendruck et al ()—wherein stickers were not presented as coming from the same set. In the latter, 4‐year‐olds were more likely to choose stickers of an abundant type.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…This difference could potentially explain the change in infants’ responding from Study 1 to Study 2. In fact, a similar change is seen when comparing 4‐year‐olds’ responses in Study 3 here—wherein all stickers were presented as coming from a single set—to the responses of 4‐year‐olds in Diesendruck et al ()—wherein stickers were not presented as coming from the same set. In the latter, 4‐year‐olds were more likely to choose stickers of an abundant type.…”
Section: Discussionsupporting
confidence: 65%
“…In Study 3, we continued tracing the development of such a bias, by moving to older participants, namely 3‐ to 6‐year‐olds. These were ages previously found to capture potential changes in children’s scarcity bias (Diesendruck et al, ; John et al, ). Given that the procedure used in Study 2 showed more promise for revealing a scarcity bias, in Study 3 we adopted the same procedure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations